Організаційно-правові питання діяльності підрозділу Литовської поліції з антитерористичних операцій «ARAS»: досвід та перспективи використання в Україні - Чумак, В. В.; Chumak, V. V.; ORCID: http://orcid.org/0000-0002-6171-2250 (Право і безпека. - 2015. - № 4 (59). - С. 102-106., 2015)
Досліджено правове регулювання діяльності підрозділу Литовської поліції з антитерористичних операцій «ARAS». Встановлено, що цей підрозділ є ключовим суб’єктом литовської національної поліцейської системи у боротьбі з тероризмом, проаналізовано його функції та завдання. Обґрунтовано доцільність використання досвіду діяльності підрозділу Литовської поліції з антитерористичних операцій «ARAS» в Україні.

Legal regulation of the activities of Lithuanian Police Anti-Terrorist Operations Unit «ARAS» has been studied. It has been found out that this unit is a key subject of Lithuanian national police system in the fight against terrorism. It has been outlined that ATLAS is international organization that consists of specialized police units of the member-states of the European Union, its objective is cooperation and mutual support and assistance in combating terrorism and improving skills, knowledge and experience of combating terrorism among law enforcement agencies – member-states ofthe European Union. It has been established that Lithuanian Police Anti-Terrorist Operations Unit «ARAS» is an independent specialized police unit, which includes command staff, department of information, analysis and negotiations, department of search and elimination of explosives, special unit, three squadrons, one of which is located in the port city of Klaipeda. Functions and tasks of Lithuanian Police AntiTerrorist Operations Unit «ARAS» have been analyzed. It has been emphasized that in conditions of a complex situation and holding anti-terrorist operation in Ukraine positive experience of Lithuanian Police Anti-Terrorist Operations Unit «ARAS» should be the object of further study and implementation in the activities of the Ministry of Internal Affairs of Ukraine and the National Police of Ukraine to improve the activities and further development of the system of Internal Affairs Agencies of Ukraine. The expediency of using the experience of Lithuanian Police Anti-Terrorist Operations Unit «ARAS» in Ukraine has been grounded.

Исследовано правовое регулирование деятельности подразделения Литовской полиции по антитеррористическим операциям «ARAS». Установлено, что это подразделение является ключевым субъектом литовской национальной полицейской системы по борьбе с терроризмом, проанализированы его функции и задачи. Обоснована целесообразность использования опыта деятельности подразделения Литовской полиции по антитеррористическим операциям «ARAS» в Украине.
Чумак, В. В. Організаційно-правові питання діяльності підрозділу Литовської поліції з антитерористичних операцій «ARAS»: досвід та перспективи використання в Україні / В. В. Чумак // Право і безпека. - 2015. - № 4 (59). - С. 102-106.
Chumak, V.V. (201 5), “Organizational and legal issues of the activities of Lithuanian Police Anti-Terrorist Operations Unit «ARAS»: experience and perspectives of using in Ukraine” [“Orhanizatsiino-pravovi pytannia diialnosti pidrozdilu Lytovskoi politsii z antyterorystychnykh operatsii «ARAS»: dosvid ta perspektyvy vykorystannia v Ukraini”], Pravo i Bezpeka, No. 4, pp. 102–106.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; Литва; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; правоохоронні органи; правоохранительные органы; Україна. Ukraine. Украина; поліція; полиция; police; антитерористичні операції «ARAS»; антитеррористические операции «ARAS»; anti-terrorist operations «ARAS»; Lithuania; Internal Affairs Agencies; law enforcement agencies; Літва; зарубежные страны; зарубіжні країни; зарубежный опыт; зарубіжний досвід; боротьба з тероризмом; борьба с терроризмом